The Effect of Think Talk Write Strategy toward Students’ Information Literacy in Immune System Concept - Barus, Lailan Safitri; Jayanti, Ummi Nur Afinni Dwi (FKIP Universitas Lampung, 2023)
Students' lack of information literacy skills are influenced by some factors, including educators' use of a learning strategy and their inability to link it to their students. The purpose of this study is to ascertain whether or not the Think Talk Write strategy enhances students' literacy abilities regarding immune system content. A non-equivalent pretest-posttest design and a quasi-experimental design were used in this research. Fifty-two of 11th grade students dari MAS Raudhatul Akmal Batang Kuis served as the sample who was chosen by cluster random sampling technique. An information literacy questionnaire was used as research instrument which was developed by following the information literacy principles. The ANCOVA test was used to analyze the data. The implementation of Think Talk Write strategy had a significant impact on students' information literacy skills.Keywords: Think Talk Write strategy, information literacy, biology learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp01-12